Placing inclusive education in conversation with digital education - Carrim, Nazir; Bekker, Tanya (South African Computer Journal, 2022)
This article places inclusive education in conversation with digital education, and it does so for two reasons. The first reason is that the increased use of digital education will need to be inclusive and should not result in increasing inequalities. The second reason is that the experience within inclusive education provides valuable insights which could benefit the development of digital education. This article is conceptually based, and its aim is to show how experiences in inclusive education could benefit the development of digital education and vice versa. It argues that like inclusive education, the increased use of digital education in the future will require a redefinition and revisioning of education. While policies and legislation as well as training in digital education are important, this article recommends that digital education will need to engage with the deep-seated values, beliefs and assumptions held by teachers, students, parents, and society at large, and will require careful attention being paid to the systematic organisation of online learning in terms of curriculum, pedagogy, and assessment just as inclusive education.
Publisher: South African Computer Society (SAICSIT)